NTRK-rearranged spindle cell neoplasm of the female genital tract: case report and literature review - Feng, Lulu; Li, Lei; He, Yanmei; Jiang, Wei (Frontiers in Oncology, 2025)
NTRK-rearranged spindle cell neoplasm is a rare subtype of soft tissue sarcoma that occasionally arises in the lower female genital tract. Accurate diagnosis is clinically important, as these tumors generally display low-grade malignant behavior and may respond to TRK inhibitor therapy. We report a rare case of cervical NTRK-rearranged spindle cell neoplasm in a 40-year-old woman who presented with abnormal vaginal bleeding. An initial biopsy of the cervical mass suggested a diagnosis of sarcoma. The patient subsequently underwent a total hysterectomy with bilateral salpingo-oophorectomy. Histological examination revealed spindle-shaped tumor cells diffusely infiltrating the cervical stroma in a solid growth pattern. Immunohistochemistry demonstrated diffuse expression of TRK and CD34. Fluorescence in situ hybridization (FISH) detected rearrangement of the NTRK1 gene, and RNA-based next-generation sequencing confirmed a TPM3::NTRK1 fusion gene. To date, only 61 cases of NTRK-rearranged spindle cell neoplasm in the female genital tract have been reported. Here, we present a new case with a detailed description of the clinical presentation, histopathological and immunophenotypic characteristics, molecular findings, and clinical outcome. Comparative analysis with previously reported cases suggests a possible correlation between NTRK fusion type and patient prognosis. Specifically, tumors with NTRK1 fusions tend to present at earlier stages and are associated with more favorable outcomes. These findings highlight the potential value of tailoring clinical management strategies based on fusion type.